A Framework for Integrated Zakat Management to Combat Poverty in Indonesia Using Analytic Network Process - Vandiantara, Surya; Al Arif, Muhammad Nur Rianto; Nafis, Cholil (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This research aims to propose an integrated zakat management model designed to decrease the number of impoverished individuals in Indonesia.Design/methodology: The study employs the Analytic Network Process (ANP) method, which involves conducting in-depth interviews with experts in the field.Findings: The main sub-indicator that dominates the zakat collection solution is the integration of collection between LAZ. Integration of central and regional distribution is the main priority in zakat distribution solutions. The main sub-indicator that dominates the zakat management solution is management integration between LAZPractical implications: Alternative strategies in the integrated zakat management model to reduce the number of poor people in Indonesia sequentially, which involve: 1) identification and mapping integration strategy, 2) digital platform, 3) certification of amil professionalism standards, and 4) urban-rural strategy.Originality/Value: There is no research that specifically discusses the integrated zakat management model to all LAZ in Indonesia